2021
DOI: 10.5530/ijpcs.2021.10.17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist’s Perception of Forensic Pharmacy Services

Abstract: Goal: To illuminate the pharmacist perception of forensic pharmacy in Saudi Arabia. Methods: It is cross-sectional of convenient sampling and planned number of the subject with power eighty. An electronic survey was dispersed to the pharmacist and pharmacy intern, excluding pharmacy students and other healthcare professionals. The survey entailed of demographic data, pharmacist's perception of forensic pharmacy, and barriers preventing implementation of forensic pharmacy. Survey monkey, Microsoft Excel, and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…[5][6][7][8] Additional research examined specific knowledge or perceptions regarding pharmaceutical care. [9][10][11][12][13] Numerous guidelines discussed the cross-sectional model in research practice and the model's advantages and disadvantages. [13][14][15][16][17][18][19][20][21][22] However, the policies and procedures for cross-sectional research are not well documented or are only found infrequently in the literature search database.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Additional research examined specific knowledge or perceptions regarding pharmaceutical care. [9][10][11][12][13] Numerous guidelines discussed the cross-sectional model in research practice and the model's advantages and disadvantages. [13][14][15][16][17][18][19][20][21][22] However, the policies and procedures for cross-sectional research are not well documented or are only found infrequently in the literature search database.…”
Section: Introductionmentioning
confidence: 99%